Electrofacies Characterization of an Iraqi Carbonate Reservoir - Abdulhadi Abdulateef, Dahlia; Zarzor, Ahmed; S. AL Jawad, Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Predicting peterophysical parameters and doing accurate geological modeling which are an active research area in petroleum industry cannot be done accurately unless the reservoir formations are classified into sub-groups. Also, getting core samples from all wells and characterize them by geologists are very expensive way; therefore, we used the Electro-Facies characterization which is a simple and cost-effective approach to classify one of Iraqi heterogeneous carbonate reservoirs using commonly available well logs. The main goal of this work is to identify the optimum E-Facies units based on principal components analysis (PCA) and model based cluster analysis(MCA) depending on available well logs data for four wells from an Iraqi carbonate oil field. The optimum E-Facies units came from comparing them with geologist classification units for these four wells. Also, we conclude that the value of permeability is not important to get the optimum E-Facies units.Several runs have been tried each with different number of units using the Electro-Facies approach. The results of the techniques show very good match of the tops for various units with the actual ones. This application also shows the power and versatility of electrofacies characterization in improving reservoir descriptions in complex carbonate reservoirs.